2021
DOI: 10.3389/fcell.2021.751578
|View full text |Cite
|
Sign up to set email alerts
|

Non-coding RNAs in Regulating Tumor Angiogenesis

Abstract: Non-coding RNAs (ncRNAs) are RNAs that do not encode proteins, but perform biological functions in various physiological and pathological processes, including cancer formation, inflammation, and neurological diseases. Tumor blood vessels are a key target for cancer management. A number of factors regulate the angiogenesis of malignant tumors. NcRNAs participate in the regulation of tumor angiogenesis. Abnormal expression of ncRNAs act as tumor suppressors or oncogenes to affect the development of tumors. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 99 publications
(138 reference statements)
0
3
0
Order By: Relevance
“…In recent years, new advances have been made in exploring the regulatory role of ncRNAs in tumor angiogenesis. For example, RNA sponges, specific interfering molecules targeting ncRNAs that are proto-oncogenes, were synthesized for anti-tumor angiogenesis therapy [ 40 ]. In conclusion, ncRNAs such as miR-199a, which regulate tumor angiogenesis, could be a target for the development of new drugs for the treatment of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, new advances have been made in exploring the regulatory role of ncRNAs in tumor angiogenesis. For example, RNA sponges, specific interfering molecules targeting ncRNAs that are proto-oncogenes, were synthesized for anti-tumor angiogenesis therapy [ 40 ]. In conclusion, ncRNAs such as miR-199a, which regulate tumor angiogenesis, could be a target for the development of new drugs for the treatment of cancer.…”
Section: Resultsmentioning
confidence: 99%
“…The administration of ncRNAs has emerged as a potential therapeutic strategy to stop tumor progression through angiogenesis suppression [101]. MiR-29b is a tumor suppressor miRNA in many cancers, where it regulates cell proliferation, apoptosis, and differentiation, and its expression also decreases in breast cancer tissue compared with normal mammary tissue [65].…”
Section: Non-coding Rnas In the Regulation Of Tam-induced Angiogenesismentioning
confidence: 99%
“…ncRNAs are functional RNA molecules that are not being translated into proteins but are involved in various physiological and pathological processes. 21 It was found that the dysregulation of certain ncRNAs is related to tumorigenesis, neurological, cardiovascular development, and other diseases. 22 In recent decades, a large number of studies have reported the key role of ncRNAs in cancer progression, metastasis, and drug resistance.…”
Section: Introductionmentioning
confidence: 99%